2017
DOI: 10.1080/15476278.2017.1344376
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a silk Fibroin/Polyurethane blend patch on rat Vessels

Abstract: Patch grafts are widely used in various kind of vascular surgeries such as detect repair or dilation of vascular stenosis. Expanded polytetrafluoroethylene (ePTFE) patches are flexible and handle well, but have shown problems with calcification as they are non-bioabsorbable and therefore permanently remain in the body. It is important to develop an alternative biocompatible patch. Silk fibroin (SF) was developed as a biocompatible material, but it lacks of the elasticity required for surgery as a patch. Polyur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Mg 2+ and Fe 3+ were shown to be able to inhibit pathological calcification in PU implants [533], with calcification also being overcome by blending a PU with silk fibroin [534].…”
Section: Calcificationmentioning
confidence: 99%
“…Mg 2+ and Fe 3+ were shown to be able to inhibit pathological calcification in PU implants [533], with calcification also being overcome by blending a PU with silk fibroin [534].…”
Section: Calcificationmentioning
confidence: 99%
“…The SF/PU patch did not present any signs of calcification for three months. This study addressed the problems associated with using SF in isolation and showed that the SF/PU patch can be considered as a useful alternative to the ePTFE to overcome the problem of calcification [20]. Additionally, we focused on the effects of different SF concentrations in the SF/PU patch on its biological and physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, studies that employed SF as an artificial vessel confirmed it to have excellent hemocompatibility, cell viability, tissue integrity, and mechanical strength [42][43][44]. SF was also incorporated into cardiovascular patches purposed for vascular surgery [41,45]. Additionally, an in vivo study confirmed SF to have favorable biological and physical properties, and that it can be effectively used in vessel reconstruction surgery [41].…”
Section: Discussionmentioning
confidence: 93%